Trajectory matching by low-cost GNSS allows continuous time comparisons during cross-country skiing - Fasel, B.; Laaksonen, M. S.; Supej, M. (Sportinformatik XII. 12. Symposium der dvs-Sektion "Sportinformatik und Sporttechnologie" vom 5.-7. September 2018 in Garching. Abstracts., 2018)
Introduction: In most endurance sports, including cross-country (XC) skiing, the fastest athlete wins the race. Successful performance requires an optimal pacing strategy i.e., effective distribution of work and energy throughout a race (Abbiss & Laursen, 2008). For any given lap of a race, no more than a few split times are usually available, due to the complex logistics of setting up a timing system. However, optimal tracking of pacing (speed) during a race requires determination of more split times at regular and shorter intervals. For example, a high-end Global Navigation Satellite System (GNSS) can be used to easily obtain a high number of split times based on a comparison of positions (Andersson et al., 2010; Supej & Holmberg, 2011). Accordingly, the aim here was to determine whether comparison of position at one-meter intervals using a standard GNSS gives reliable split times during XC skiing.